"I Didn't Know I Could do That!" Student and Teacher Perceptions of an Independent Choral Music Learning Project. (February 2021) - Haning, Marshall
Through the use of an intrinsic case study, I investigated student and teacher perceptions of a collaborative and student-directed music learning approach in a high school choral classroom. Students ( N = 29) in a beginning high school choir were asked to choose and learn a piece of repertoire without substantive input or help from the choral teacher. Results indicated that students completed this project successfully and achieved a well-received public performance of the piece. Students reported a strong sense of accomplishment as well as increased collaboration skills and opportunities to apply their music knowledge. Although students and teacher acknowledged some social conflicts and relatively high levels of social loafing and off-task behavior during this project, these challenges did not seem to reduce the overall perception of success.